Can This Dog Be Rehomed to You? A Qualitative Analysis and Assessment of the Scientific Quality of the Potential Adopter Screening Policies and Procedures of Rehoming Organisations - Griffin, Karen E.; John, Elizabeth; Pike, Tom; Mills, Daniel S. (Frontiers in Veterinary Science, 2020)
Unwanted dogs are an international problem, and rehoming organisations are tasked with finding many of them appropriate homes. Whilst the processes involved in assessing dogs' suitability for rehoming have received considerable academic attention, the policies and procedures organisations employ for screening potential adopters, which are equally as important to dogs' outcomes, appear to be largely overlooked. Therefore, the aim of this study was to conduct a qualitative analysis of rehoming organisations' adopter screening processes in order to gain insight into what is being done, the extent to which this appears to have any scientific rationale, and what other factors might be driving the process. A written enquiry was sent to organisations in the UK; topics addressed included whether they use a standardised screening process, whether they interview potential adopters and what information is gathered during the interview, and how they score responses. Information was received from 82 respondents. Pre-adoption home visits were the most commonly used method. Self-administered questionnaires were the most standardised method. Using a thematic analysis, ten themes emerged from the types of information gathered during the screening process; 31 characteristics could lead an adopter being deemed unsuitable to adopt a dog. Evidence to potentially support these was found for only eight of them in the academic literature relating to risk factors for relinquishment and human safety risk. The inclusion of some of the characteristics considered important was thought to be for the purpose of ensuring a good quality of life for a dog, but there is a lack of relevant research investigating this. Organisations seem to invest considerable resources into screening potential adopters, but there is limited scientific, and sometimes logical, rationale for this. A further concern relates to the quality of the assessment processes, which show little evidence of quality control measures. Until the necessary research is conducted, it could be argued, from a pragmatic perspective, that organisations should relax their strict screening criteria, and focus their resources on ensuring owners are fully prepared for the changes in their life associated with the inclusion of a new dog in their home and supporting them as necessary.